Ingestão da tintura de valeriana officinalis protege da discinesia orofacial induzida por reserpina em ratos - Pereira, Romaiana Picada (2009)
Considering the hypothesis that GABA and oxidative stress are involved in the development of oral movements associated with important neuropathologies, the present study investigated the possible ability of V. officinalis in the prevention of vacuous chewing movements (VCMs) induced by reserpine in rats. Adult male rats were treated with reserpine (1 mg/kg, s.c.) and/or with V. officinalis (in the drinking water). VCMs, locomotor activity and oxidative stress measurements were evaluated. The neuroprotective effect of V. officinalis against iron-induced cell toxicity was investigated in brain cortical slices. Furthermore, we carried out the identification of valeric acid and gallic acid by HPLC in the V. officinalis tincture. Our findings demonstrate that reserpine caused a marked increase on VCMs and the co-treatment with V. officinalis was able to reduce the intensity of VCM. Reserpine did not induce oxidative stress in cerebral structures (cortex, hippocampus, striatum and substantia nigra). However, a significant positive correlation between DCF-oxidation (an estimation of oxidative stress) in the cortex and VCMs (p<0.05) was observed. Moreover, a tendency for a negative correlation between Na+K+- ATPase activity in substantia nigra and the number of VCMs was observed (p= 0.06). In vitro, V. officinalis protected brain cortical slices viability against Fe(II)-induced neurotoxicity. In conclusion, V. officinalis had in vitro and in vivo neuroprotective effects in rats, i.e., reduced Fe(II) neurotoxicity and reserpine-induced VCMs, probably via modulation of oxidative stress in specific brain nucleus and its GABA-mimetic action. However, the mechanisms involved in this protective activity needs to further investigated to better understand the action of V. officinalis.